PENGARUH SERVICE QUALITY TERHADAP SWITCHING BEHAVIOR PENGGUNA SIM CARD TELKOMSEL - Fakhrurrazi Amir; T. Meldi Kesuma (Faculty of Economics and Business, Universitas Malikussaleh, 2017)
The aims of this study are to investigate the effect of service quality and innovationon switching behavior. Colleger of Syiah Kuala University as the consumers ofSubscriber Identity Module card Telkomsel is taken as a sample in this study. Themethod of this study employed questionnairs as an instrument. Total sampling is appliedas the study’s proportional technique. Hierarchical Linear Modelling methodsof analysis are used to determine the influence of the variables involved. The resultof this study indicates that service quality have positive effect on switching behavior,service quality have positive effect on innovation, and innovation has positive effecton switching behavior. The study also shows that innovation influential significantlyagainst service quality nor against switching behavior. In addition abtained resultsthat innovation has partial mediated the effect of service quality to impulse switchingbehavior.